A Wireless Healthcare System Based on Mobile Internet Platform - Jun Yan; Chao Chen; Xiaohui Duan; Anpeng Huang; Zhinan Li (2010 2nd International Conference on Information Engineering and Computer Science, 2010)
This design combines sensor network, embedded system, Internet information service and database to provide patients a safe, easy and integral wireless healthcare system. Safety is ensured by the advantage of applications based on Windows Mobile. Moreover, the GUI made it possible for elder patients to use the software easily, while Internet Health Service makes the healthcare be more integral.